Comparing cooling energy between existing air-conditioning system and proposed design system - Syazwan, M. M. Syafiq; Yusof, M. Z. M.; Chang, C.K.; Abdullah, M. D Amir (Trans Tech Publications, 2015)
Air-conditioning (AC) system is typically used to remove the sensible and latent heat loads in buildings. It provides cool and dehumidified air to meet the occupants comfort and good indoor air quality (IAQ). Improper design and analysis of AC process resulted in high cooling energy and unsatisfied indoor humidity level in tropical climate. The objective of this study is to identify the cooling energy in hotel restaurant by comparing the design with proper fresh air ventilation design. The hotel restaurant was designed with primary air unit (PAU) and air handling unit (AHU) as to remove sensible and latent loads. The performance of the AC system has been monitored and analysed using psychrometric chart. For the AC air side system, 296.2 kW of cooling energy was used in standard operation. An alternative design was proposed for the said hotel restaurant employing only one AHU, with a cooling capacity of 165.9 kW which was 43 % lower than the existing system. The difference in temperature, humidity ratio and air flow rate influenced the cooling energy for AC system.